2018
DOI: 10.1186/s12936-018-2376-4
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of malaria pre-elimination in Cape Verde according to the data collected from 2010 to 2016

Abstract: BackgroundMalaria, despite being preventable and treatable, continues to be a major public health problem worldwide. The archipelago nation of Cape Verde is in a malaria pre-elimination phase with the highest potential to achieve the target goal of elimination in 2020.MethodsNationwide malaria epidemiological data were obtained from the Cape Verde health information system that includes the individual malaria case notification system from all of the country’s health structures. Each case is reported to the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 7 publications
7
28
0
Order By: Relevance
“…To ensure elimination can be sustained and to support the prevention to reintroduction phase, the malaria case data collected as part of routine surveillance from the decade before interruption can be valuable for characterizing the malaria epidemiology and identify risk factors for improved surveillance activities. Therefore, this research extends previous research about malaria cases in the country [13,14] and characterizes both individual and spatial risk factors for endemic and introduced malaria infections.…”
Section: Introductionsupporting
confidence: 71%
“…To ensure elimination can be sustained and to support the prevention to reintroduction phase, the malaria case data collected as part of routine surveillance from the decade before interruption can be valuable for characterizing the malaria epidemiology and identify risk factors for improved surveillance activities. Therefore, this research extends previous research about malaria cases in the country [13,14] and characterizes both individual and spatial risk factors for endemic and introduced malaria infections.…”
Section: Introductionsupporting
confidence: 71%
“…Differently from the transition by gametocytemia variation, here the phase transition is only visible for high gametocytemia levels, typically w h = 0.6 or larger. A possible explanation for this is 6 There is no precise knowledge concerning the probability for the mosquito to die due to ITN, IRS or LLIN barriers. We assumed a value of 0.5, which together with a coverage of ITN of 25%, results in a global mortality due to ITN barriers of 0.25 × 0.5 = 0.125.…”
Section: The Role Of Ivermectin In Transmission Preventionmentioning
confidence: 99%
“…For example, in a potential outbreak human fatality rate may rise out of proportion due to the weaker immunity of local populations from reduced exposure to the parasite [5]. Or, in regions under anti-malaria massive drug administration, drug-resistant parasite strains can develop and consequently, through human migratory phenomena, they may be imported into areas of near eradication, locally strengthening malaria transmission [2,3,6].…”
Section: Introductionmentioning
confidence: 99%
“…island, Praia came at second position with 2.16%. Noteworthy, Santiago was the only study island of Cabo Verde where indigenous malaria cases were reported during the last three years [4,5], stressing the interest of such study in the different municipalities of the island. The prevalence of G6PDd in the Cape Verdean population was higher in males (5.7%) than females (1.6%) ( Table 2).…”
Section: Plos Onementioning
confidence: 99%
“…Historically, malaria has been the first vector-borne disease in Cabo Verde since the 16 th century during the settlement of the islands, and with some efforts, the disease has been eliminated twice from the archipelago. In the last years, the malaria epidemiological situation has become unstable with the sporadic seasonal transmission, and local transmission exclusively occurring in Santiago and Boavista islands [4,5].…”
Section: Introductionmentioning
confidence: 99%